Bong's day - Villanueva, Rene O.; Cruz, Nemcy (Quezon City Adarna House, 2004)
This book illustrates the progress of a day in the life of Bong, up to the first hours of the night. This story can help teach children how to tell time and make them more aware of its passing.
Keywords: Time -- Juvenile literature